Asymmetric Digital Subscriber Line (ADSL) - Šarić, Slavko; Peraković, Dragan; Brdar, Gordan (Promet - Traffic&Transportation, 2012)
ADSL (Asymmetric Digital Subscriber Line) is a technologythat allows transmission at 8.488 Mbps over the existingtelephone copper line (speed range depending on the distance).ADSL circuit connects the ADSL modems by twisted-pairtelephone lines creating three infonnation channels: high speedsimplex (maximum 9 Mbps), medium speed duplex channel(maximum 2 Mbps) and plain old telephone service channel.ADSL technology supports up to seven synchronous channelsthat can be configured to meet the needs of the end user.One could simultaneously view four movies stored in MPEG 1fonnat on separate television sets (MPEG 1 transmitted at 1.5Mbps), hold a video-conference (transmitted at 348 kbps),download data files from a server at 128 kbps via ISDN andeven receive a telephone call.